Can CRP Levels Predict Infection in Presumptive Aseptic Long Bone Non-Unions? A Prospective Cohort Study - Tosounidis, Theodoros H. (J Clin Med, 2021)
Nonunion remains a major complication of the management of long bone fractures. The primary aim of the present study was to investigate whether raised levels of C-reactive protein (CRP) and white blood cell count (WBC), in the absence of clinical signs, are correlated with positive intraoperative tissue cultures in presumptive aseptic long-bone nonunions. Infection was classified as positive if any significant growth of microorganisms was observed from bone/tissue samples sent from the theater at the time of revision surgery. Preoperatively all patients were investigated with full blood count, white blood count differential as well as C-reactive protein (CRP). A total of 105 consecutive patients (59 males) were included in the study, with an average age of 46.76 years (range 16–92 years) at the time of nonunion diagnosis. The vast majority were femoral (56) and tibial (37) nonunions. The median time from the index surgical procedure to the time of nonunion diagnosis was 10 months (range 9 months to 10 years). Positive cultures revealed a mixed growth of microorganisms, with coagulase-negative Staphylococcus (56.4%) being the most prevalent microorganism, followed by Staphylococcus aureus (20.5%). Pseudomonas, Methicillin-Resistant Staphylococcus aureus (MRSA), coliforms and micrococcus were present in the remainder of the cases (23.1%). Overall, the risk of infection with normal CRP levels (<10 mg/L) was 21/80 = 0.26. Elevated CRP levels (≥10 mg/L) increased the risk of infection to 0.72. The relative risk given a positive CRP test was RR = 0.72/0.26 = 2.74. Overall, the WBC count was found to be an unreliable marker to predict infection. Solid union was achieved in all cases after an average of 6.5 months (3–24 months) from revision surgery. In patients with presumed aseptic long bone nonunion and normal CRP levels, the risk of underlying low-grade indolent infection can be as high as 26%. Patients should be made aware of this finding, which can complicate their treatment course and outcomes.